(3GdCOH GdLGeYs - (3YHO Gddg Hf GdebaY , GHf GdebaY , CHh YeQ,J (B142 (3g` s ((3KZQ GdCScfOQjI s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje EfG hLOfG GdfGS bHdfG cGfhG CYXe CLSGekG, hCYXe eY CLSGege CMdGekG, hCfTO eY bhJge ddCehQ (B((3EeJMGfkG(B)(3, hCWhd CYeGQkG s
(3BNQgG (B:s
(3hdG jZQfc Pdc ef faSc Ydi Jdc GdMGd aEfgG djSJ RgGOkI hdcf VLQkG hJZjQ faS hdcf EPG OYJc faSc Edi QaV GdOfjG aCSQY ELGHJgG Je cJGH GdCOH GdLGeY s
(3HChd GdeNWhW hBNQg JbjjOGJ heWGdYGJ hJedjcGJs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B140 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B156s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B13 s
Keywords: (3GdCOHs